Interaction Assessment of Stress Intensity Factors of Surface Cracks on Thick Cylinders under Tension Force and Bending Moment - Al-Moayed, Omar Mohammed; M.F, Johan; Ismail, Al Emran; Kareem, Ali Kamil; Jamian, Saifulnizan; Shaker, Sufian Farid; Hamad Abed, Tareq; Aldulaym, Omar Hammad (semarak ilmu, 2024)
From an engineering perspective, hollow cylinders have various applications in the industry due to their strength, versatility, and geometric properties, making them vital for various applications in diverse industries. Therefore, it could be seen in many aspects such as fluid conveyance, manufacturing and fabrication, rotating machinery, structural components, storage, and pressure vessels. As it is well-known fracture is the most dominant type of failure in cylinders that is caused by defects or flaws. With time, these cracks (flaws) may extend and lead to a tragic failure, posing significant risks to both the nearby environment and humans. Moreover, crack cooperation which is known as (crack interaction) represents a chief apprehension, where cooperation or interaction may accelerate the crack growth and cause unpredictable failure. In this work, a wide variety of crack configurations were examined to quantify the interaction of double-interacting surface cracks located on a thick cylinder numerically via ANSYS software. The Stress Intensity Factor (SIFs) has been utilized as a driving force to describe the crack interaction. The results found that crack interaction influenced both cracks by the same rate, and SIFs distributed along the crack front by the same style as that of a single crack. Also, an inversely proportional relationship has been found between the crack interaction and the separation distance between the cracks. It is possible to conclude that the crack interaction of double interacting cracks exhibited a shielding effect, where SIFs for the case of double cracks were less than those of single crack.